Innovative time and attendance system software selection for a private hospital: leveraging the entropy-TOPSIS method / Norazean Nordin ... [et al.] - Nordin, Norazean; Samat, Eaisya Nurfarhana; Adam, Fairuz Noraainaa; Mahadi, Nor Faradilah (UiTM Cawangan Perlis, 2024)
Automated time and attendance systems offer the capability to track employee attendance, calculate working days, overtime hours, and late arrivals, and generate comprehensive attendance reports, thereby improving workforce productivity. Investing in suitable time and attendance system software is crucial for a company since many businesses are adopting digital time and attendance systems that automatically collect and analyse data to increase productivity and efficiency. This decision-making process considers numerous contradictory criteria. Thus, for this study, the Multi-Criteria Decision Making (MCDM) methods, namely Entropy and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), were used to choose the best time and attendance system software for a private hospital. There were six (6) criteria used to evaluate the time and attendance system software. The criteria were categorised as cost ease of use being compatible with existing HR software and operating system reporting capabilities customer service and scheduling capabilities Meanwhile, the alternatives are labelled as The outcomes showed that the ranking order for the criteria is while the ranking order for the alternative is respectively. In conclusion, the Entropy-TOPSIS can be used to assess and rank the alternatives.